Ethical issues in long-term care settings: Care workers' lived experiences - Arjama Anna-Liisa; Suhonen Riitta; Kangasniemi Mari (SAGE PUBLICATIONS LTD, 2025)
Background Professional care workers face ethical issues in long-term care settings (LTCS) for older adults. They need to be independent and responsible, despite limited resources, a shortage of skilled professionals, global and societal changes, and the negative reputation of LTCS work.
Research aim Our aim was to describe the care workers' lived experiences of ethical issues. The findings can be used to gain new perspectives and to guide decision-making to improve the quality of care, occupational well-being and nursing education.
Research design Focus group interviews were analyzed using a hermeneutic-phenomenological method. The analysis comprised three steps: naive reading, structural analysis, and comprehensive understanding.
Participants and research context We randomly sampled LTCS service providers in Finland and 53 care workers with different educational backgrounds from seven organizations participated in focus group interviews in 2021.
Ethical considerations This was a sensitive study, which was connected to the participants' individual views of the world, professional ethics and social and health care legislation. The participants' provided informed consent and their anonymity was guaranteed.
Findings Care workers spoke about their lived experiences of ethical issues in an emotional way, using practical examples. They talked about how they were experts at caring and advocating for residents, balanced the responsibilities of their different roles, and defended their work to the wider society. The care workers said that ethical aspects of their work were too difficult to solve on their own. There were elements of their working environment and practices that caused unnecessary strain and they needed the commitment of managers, organizations, and society to solve ethical issues in LTCS.
Conclusions Ethical issues were related to the well-being of both residents and care workers and reflected both internal and external pressures. Some issues could not be resolved by individuals and needed input from managers, organizations, and society.